Toward a Presentist Pedagogy of Interest. Issue 6 (12th March 2020) - Zipory, Oded
Abstract: In this essay, Oded Zipory assigns a different meaning to presentism in education: one that signifies respect for the present, especially for the actual student in his here‐and‐now. Zipory suggests that the key component of such a presentist pedagogy is interest and argues that focusing on children's current and possible interests instead of, or at least in addition to, working toward their expected future achievement is both respectful of children as meaning‐makers and promising in regard to their autonomy. First, he lays out principles for a presentist pedagogy of interest. Following Harry Frankfurt's work on the concept of care, Zipory suggests that schools should pay attention to the fact that students care about various things in addition to focusing on children's required knowledge and desired behavior. He then shows that being interested in something is a particular form of caring about it, and that this form is closely connected to education and learning. After showing the importance of interests to education, Zipory presents the challenges to incorporating them into a curriculum, and, drawing on P. S. Wilson's work, suggests strategies for coping with these challenges. He concludes by addressing the temporal tension embedded in the word "interest" itself and suggests that, in order to distance education from instrumentalization and commodification, a present‐oriented meaning of interest should be adopted.